Overconfidence and Gender Differences in Wage Expectations - Sascha Satlukal; Stephanie Briel; Mirjam Reutter; Gregor Pfeifer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We analyze the impact of overconfidence on gender differences in wage expectations using elicited beliefs of German university applicants. Interestingly, female students have lower wage expectations and are less overconfident than their male counterparts. Oaxaca-Blinder decompositions show that a substantial part (7.6%) of the gender gap in wage expectations can be explained by stronger overconfidence of males. Applying recentered influence function decompositions, we find that the impact of overconfidence on the gender gap is particularly strong at the bottom and top of the wage expectation distribution, suggesting that females with the lowest expectations feature a very low level of confidence while males with the highest expectations feature a very high level of confidence.
Keywords: J16; D84; D91; C21; 330; Gender Pay Gap; Wage Expectations; Overconfidence